Assessment of Potential Area in Jakarta Capital City Based on Land Performance Weighting - Rosantiningsih, Ika; Hasan, Chotib (UI Scholars Hub, 2024)
Law of the Republic of Indonesia No. 3 of 2022 concerning the National Capital has a major impact on Jakarta, challenges for Jakarta to response the relocation of the capital. Jakarta strives to become a Global City by increasing investment, various efforts are made for increasing and economic stabilitation, in line with the sustainable development goals,